On the role of general purpose technologies within the Marshall-Jacobs controversy: The case of nanotechnologies - Nina Menz; Ingrid Ott (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
This paper investigates the role of nanotechnologies as a general purpose technology for regional development. Due to pervasiveness, nanotechnologies may be utilized in diverse applications thereby providing the basis for both localization and urbanization externalities. We carry out patent and publication analyses for the city state of Hamburg during the period 1990-2010. We find evidence that nanotechnologies are advanced in the context of regional knowledge bases and follow up prevailing specialization patterns. As nanotechnologies develop both industry specific and city specific externalities become effective leading to specialization deepening and specialization widening which both are functions of the increasing nano-knowledge base.
urn:nbn:de:swb:90-225882
Keywords: R11; O31; 330; general purpose technology; nanotechnology; specialization; diversification; Marshall-Jacobs controversy; patent and publication analysis